Gastric variceal obstruction improves the efficacy of endoscopic management of esophageal variceal bleeding in GOV type I - Huang, Xiaoquan; Zou, Detong; Wang, Huishan; Chen, Wei; Zhang, Lili; Li, Feng; Ma, Lili; Zhang, Chunqing; Chen, Ying; Chen, Shiyao (Endoscopy International Open, 2024)
Background and study aims Limited data exist regarding endoscopic obstruction of type I gastroesophageal (GOV I) in managing bleeding from esophageal varices. In this multicenter retrospective cohort study, we aimed to access the efficacy of blocking gastric varices in management of bleeding from esophageal varices in patients with GOV1.Patients and methods Cirrhotic patients experiencing bleeding from esophageal varices and having GOV I gastric varices in four centers were screened. All included patients were followed up for 180 days, or until death.Results A total of 93 cirrhotic patients with GOV I and bleeding esophageal varices were included. Among them, 58 patients underwent endoscopic cyanoacrylate injection (ECI) for gastric varices in addition to treatment for esophageal varices (EV), while the remaining 35 patients received treatment for EV only. Kaplan-Meier analysis demonstrated that the cumulative 180-day rebleeding rate was significantly lower in the ECI plus EV treatment group (7.9%) compared with the EV treatment group (30.7%) (P = 0.0031). The cumulative incidence of 180-day mortality was 1.9% in the ECI plus EV treatment group and 23.9% in the EV treatment group (P = 0.0010). Multivariable Cox regression analysis revealed that concomitant ECI treatment was an independent protective factor against 180-day rebleeding and overall mortality.Conclusions In conclusion, obstruction of gastric varices in addition to endoscopic treatment for bleeding from esophageal varices in patients with GOV 1 proved superior to endoscopic treatment alone for esophageal variceal bleeding.
Keywords: Endoscopy Upper GI Tract; Portal hypertension and variceal bleeding; Dilation, injection, stenting; Quality and logistical aspects; Performance and complications